Intensyfikatory treści w dyskursie religijnym = Content intensifiers in a religious discourse - Kulwicka-Kamińska, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article features an attempt at indicating intensifiers and their functions in a religious discourse. Therefore, the object of research constitutes linguistic means which serve the purpose of intensification of content at the level of the formal (grammatical and syntactic) and semantic structure of an utterance.
Keywords: dyskurs religijny; intensyfikator; przekłady; Koran; tefsir; filomaci; religious discourse; intensifiers; translations; the Quran; Philomaths